Proceedings of the International Conference on Teacher Training and Education 2017 (ICTTE 2017) 2017
DOI: 10.2991/ictte-17.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Anxiety, School Burnout and Well-Being in High School Students

Abstract: School as center of adolescent social life has an important role to help students to achieve well-being. But in fact, adolescence is often vulnerable to individual problems such as stress, anxiety, and self-destructive behavior. The current study examined the mediation effect of state and trait anxiety in the association between school burnout and well-being. State-Trait Anxiety Inventory (STAI), School Burnout Inventory (SBI), and Satisfaction with Life Scale (SWLS) was administered to 192 vocational high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Andriyani et al [55] studied the well-being of students in Indonesia as a predictor of trait and state anxiety, as a result of generalized anxiety. The authors suggested that teachers and managers need to develop school programs that can improve students' well-being, providing new school activities and services that can make students feel comfortable and thrive in schools, preventing school dropout.…”
Section: Interpretation Of Results and Final Considerationsmentioning
confidence: 99%
“…Andriyani et al [55] studied the well-being of students in Indonesia as a predictor of trait and state anxiety, as a result of generalized anxiety. The authors suggested that teachers and managers need to develop school programs that can improve students' well-being, providing new school activities and services that can make students feel comfortable and thrive in schools, preventing school dropout.…”
Section: Interpretation Of Results and Final Considerationsmentioning
confidence: 99%
“…When someone enjoys being together with other students in the class, participating in class actively, and full of energy, it is proven to reduce academic anxiety when counseling practice. That is because positive attitudes towards other groups can support wellbeing and reduce anxiety [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…When someone enjoys being together with other students in the class, participating in class actively, and full of energy, it is proven to reduce academic anxiety when counseling practice. That is because positive attitudes towards other groups can support well-being and reduce anxiety [22,23].…”
Section: Discussionmentioning
confidence: 99%